The inflection point: α-Klotho levels and the risk of all-cause mortality - Song, Jianling; Li, Hong; Fang, Xiangdong (Frontiers in Endocrinology, 2025)
PurposeThe controversial nature of the association between α-Klotho and mortality risk in the general population warrants further investigation. This study aims to examine the correlation between circulating α-Klotho levels and the risk of all-cause mortalityMethodsA sample size of 13,748 individuals from the NAHNES 2005-2016 cycles was included in this study. The effect of different α-Klotho levels (divided into quartiles) on survival was assessed using Kaplan-Meier (KM) curves. Cox proportional hazards models were used to analyze the linear relationship between log α-Klotho and the risk of all-cause mortality. Restricted cubic spline Cox proportional hazards regression model was used to analyze the non-linear relationship between log α-Klotho and risk of all-cause mortality. Threshold effect analysis was performed to determine the most favorable inflection point for log α-Klotho. Stratification and sensitivity analyses were performed to assess the robustness of the results.ResultsA total of 1,569 deaths were reported during the median follow-up period of 5.33 years (2.83-7.83 years). Among the log α-Klotho quartile groups, quartile 1 had the highest mortality rate compared to quartiles 2, 3, and 4. Multifactorial Cox regression analysis revealed a weak association between log α-Klotho and a 44% reduction in the risk of all-cause mortality (p=0.0473). We also found a U-shaped non-linear association between log α-Klotho and risk of all-cause mortality, with an optimal inflection point identified at 2.89 pg/mL. The stability of the U-shaped association between log α-Klotho and mortality risk was observed in various stratification and sensitivity analyses.ConclusionThis study identified a U-shaped association between circulating α-Klotho levels and risk of all-cause mortality, with a notable inflection point at 2.89 pg/mL. Further investigation is warranted to fully elucidate the potential mechanisms underlying the association between α-Klotho and risk of all-cause mortality in the broader population.